The Environmental Responsibility Framework: A Toolbox for Recognizing and Promoting Ecologically Conscious Research. Issue 4 (30th March 2023) - Murray, Desneiges S.; Cole, Isabel; Nunez, Nicholas; Parker, Eric M.; Mikulis, Anna; Herreid, Allison M.; Donovan, Mitchell; Fazekas, Hannah M.; Wymore, Adam S.
Abstract: Ethical guidelines have provided a cornerstone for morally appropriate research on human or other vertebrate animal subjects since at least 1945. By contrast, although there are environmental impacts associated with all science research activities (including field, laboratory, and computational projects), no comprehensive guiding framework to determine environmentally responsible research practices has been proposed. Drawing from existing models within social, medical, and animal sciences, we propose a framework for explicitly incorporating environmentally focused ethics into scientific research. The Environmental Responsibility 5‐R Framework (ER 5 F) is centered around Recognition, Refinement, Reduction, Replacement, and Restoration. ER 5 F starts with Recognizing that research can have environmental consequences, while each subsequent "R" serves as an opportunity for acknowledging, evaluating, and mitigating the environmental impacts of scientific research. These R's include: Refining research questions, Reducing the resources and energy consumed, Replacing materials with sustainable options and altering methods, and in the case of field research, Restoring an environment to mitigate any harm done. By introducing this novel and approachable framework, we strive to promote enhanced awareness across the entire scientific community by encouraging researchers to recognize their responsibility and identify potential mitigation opportunities for the environmental consequences of their research activities. We affirm that in doing so, scientists can more effectively balance the dual goals of maximizing their novel research outputs while minimizing possible harm to the environment. Key Points: Human ethos has provided a cornerstone for research on human and vertebrate subjects We propose a framework for explicitly incorporating environmentally focused ethics into scientific research The Environmental Responsibility 5‐R Framework is centered around 5‐R's: Recognition, Refinement, Reduction, Replacement, and Restoration